Should National Environmental Policy focus on developing more oil resources or developing renewable energy sources? - Utpal Kumar Nandy; Shravani Nandy; Antara Nandy (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2018)
United Arab Emirates (UAE) is a nation which is gifted with abundant reserves of oil and natural gas, thus occupying seventh position in the world. Because of its vast reserves, the oil sector plays a pivotal role in running the economic system of nation. Though the country has been making steady progress in other industries such as real estate, tourism, aviation etc. the oil industry holds the key role in its sustenance and development. However, at the same time the world is threatened by the rapidly depleting natural resources like coal and petroleum. While on the other hand their demand is on a sharp rise, due to the constantly growing population and their needs. The capital city of UAE, Abu Dhabi too is witnessing a steeply rising population level due to several factors like immigration of expatriates. With the growth in population, the pressure on the available resources is increasing exponentially.  Besides this, the UAE has the largest carbon-foot-print in the world. Thus, it is essential to develop the renewable energy resources simultaneously, which will help to conserve the natural resources apart from supporting the economy and enhancing the energy security of the country. The paper attempts to journey through certain prominent measures taken by UAE in this direction and their respective consequences [1].